Implementasi Etika Aperatur Sipil Negara dalam Pelayanan Publik di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Padang-Pariaman - Sintari Arfita; Roni Ekha Putera; Aidinil Zetra (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
The ethics of state civil servants (ASN) in providing public services has so far received special attention in order to realize quality public services. This study aims to determine and assess the Behavioral Standards of the State Civil Apparatus in Improving Public Services at the Civil Registry Service Office of Padang Pariaman Regency. The research method used is qualitative with a case study approach. The results of the researchers found that the standard of behavior of the state civil servants (ASN) at the Dukcapil Service of Padang Pariaman Regency went well. This is marked by the existence of several awards obtained by the Civil Registry Service Office of Padang Pariaman. Based on the theory initiated by Kumorotomo (2013), there are three important ideas in administrative ethics. First, ASN order. Every work action carried out by every ASN at the Civil Registry Service Office of Padang Pariaman Service will get results after an assessment, which is given rewards and punishments based on behavioral assessments. Second, the efficiency of ASN performance, the quality of ASN performance at the Civil Registry Service Office of Padang Pariaman is the result of ongoing trainings held by the Civil Registry Service Office of Padang Pariaman. The third awareness of ASN as a Public Administrator, in this case the Civil Registry Service Office, Service has a standard of behavior that is addressed to all ASN and employees/officers and is stated in the Rules of Value and behavioral guidelines at the Dukcapil Service of Padang Pariaman Regency.